2019
DOI: 10.1002/fsn3.930
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring bilberry powder functionality through processing: Effects of drying and fractionation on the stability of total polyphenols and anthocyanins

Abstract: Bilberries are a rich natural source of phenolic compounds, especially anthocyanins. The press cake obtained during the processing of bilberry juice is a potential source of phytochemicals. The objective of this study was to evaluate different drying techniques and the fractionation of bilberry press cake powder toward obtaining phenolic‐rich ingredients for incorporation into value‐added food products. The derived powders were dispersed in water and dairy cream, to investigate the effects of drying and fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This fruit is consumed not only in a fresh manner, but also in processed products (press cake) and derivatives (juice, jam and liqueur) [95,96]. Fruits drying and its transformation into powder represent a suitable alternative widely used by consumers and the food industry that allow having them available throughout the year for subsequent use as an ingredient in based foods (extruded products, bakeries, sauces, beverages, ice creams, yogurts, and confectionary) [11,97]. The by-products resulting from the production of bilberries, as well as the fruits that, due to their exterior appearance or size do not meet commercialization standards, may also be used for the preparation of polyphenols extracts and the production of novel foods, conferring them added value and reducing the environmental impact.…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…This fruit is consumed not only in a fresh manner, but also in processed products (press cake) and derivatives (juice, jam and liqueur) [95,96]. Fruits drying and its transformation into powder represent a suitable alternative widely used by consumers and the food industry that allow having them available throughout the year for subsequent use as an ingredient in based foods (extruded products, bakeries, sauces, beverages, ice creams, yogurts, and confectionary) [11,97]. The by-products resulting from the production of bilberries, as well as the fruits that, due to their exterior appearance or size do not meet commercialization standards, may also be used for the preparation of polyphenols extracts and the production of novel foods, conferring them added value and reducing the environmental impact.…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…Cyanidin‐3‐sophoroside from Garcinia mangostana rind effectively reduced activity of TY 26 . Delphinidin‐3‐O‐galactoside (DG), a natural water‐soluble anthocyanidin, is widely distributed in grapes, berries, plants, vegetables, and fruits 27–32 . No study on the interaction between DG and TY has been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…26 Delphinidin-3-O-galactoside (DG), a natural watersoluble anthocyanidin, is widely distributed in grapes, berries, plants, vegetables, and fruits. [27][28][29][30][31][32] No study on the interaction between DG and TY has been reported so far. The structure of DG is shown in Figure 1.…”
mentioning
confidence: 99%
“…This is the first part of a two‐step study where the bilberry powder functionality is tailored by effects from the whole production process including pretreatments, drying techniques, and post‐treatments. In the second part, Oliveira et al () describe the effects of drying and fractionation on the stability of polyphenols and anthocyanins in bilberry press cake powder.…”
Section: Introductionmentioning
confidence: 99%